ความพึงพอใจของผู้ปกครองของนักเรียนบัลเล่ต์ ต่อส่วนประสมการตลาดบริการของโรงเรียนเต้นและดนตรีวิวาเช่ - สกล ชาวแพรกน้อย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this independent study was to study the satisfaction of ballet students’ parents towards service marketing mix of Vivace Dance and Music School. The study was based on the concept of marketing mix which consists of product, price, place, promotion, personnel, physical evidence, and process. The data was collected from all 190 parents of students at Vivace Dance and Music School. The data was analysed using descriptive statistics namely frequency, percentage and mean. The results of the study showed that most of the parents were female, 31-40 years old, with Bachelor’s degree. Most were in business or had a business of their own with average monthly income of more than 60,000 baht. Most parents sent one child to Vivace Dance and Music School for weekend classes. The students had been to Vivace for more than one year. Most students were at pre-primary ballet. The parents chose Vivace because of the convenient location. Most students had not had ballet lessons before and the parents also had no knowledge of ballet before. Most parents learned about Vivace Dance and Music School from other parents. From the study of marketing mix, it was found that the parents ranked the overall factors in the high level in the following order, along with the sub-factor which was ranked the highest in each category. The factor that was ranked first was personnel, and the sub-factor which was ranked the highest was the staff were polite. For physical appearance, the school was safe. For process, the service was always up to the standard. For product, the lesson was appropriate for the students. For price, the price was reasonable considering the quality of teaching. For place, the location of the school was convenient. For promotion, trial lessons were offered before parents and students made the decision to learn ballet. For the satisfaction of the parents, it was found that the parents were satisfied with the overall marketing mix at the high level in the following order, along with the sub-factor which was ranked the highest in each category. The factor that was ranked first was personnel, and the sub-factor which the parents were satisfied with the most was the staff were polite and were friendly towards the parents, the students, and other customers. For physical appearance, the school had a warm atmosphere. For process, the service was always up to the standard. For product, lesson periods were appropriate. For price, the price was reasonable considering the quality of teaching, and the payment was one-time payment with no additional fees. For place, the location of the school was convenient. For promotion, trial lessons were offered before parents and students made the decision to learn ballet. From Important-Performance Analysis (IPA), it was found that most sub-factors were in Quadrant B (Keep up with good work). All sub-factors of personnel, physical evidence, and process; 3 sub-factors of product; and one sub-factor of price, place and promotion, were in Quadrant B. In Quadrant C, there were 5 sub-factors of promotion, 2 sub-factors of place, and 2 sub-factors of price. No sub-factor of product was in Quadrant C. In Quadrant D, there were 2 sub-factors of price and product, and one sub-factor of place. Therefore Vivace School had no immediate problems to solve but the school can handle these problems in time as they affected the customers at the low level. No sub-factor was found in Quadrant A (Concentrate here).